2006
DOI: 10.4049/jimmunol.177.9.6460
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Contributes to Allergen-Induced Airway Inflammation in Experimental Asthma

Abstract: Lack of sufficient IL-12 production has been suggested to be one of the basic underlying mechanisms in atopy, but a potential role of IL-12 in established allergic airway disease remains unclear. We took advantage of a mouse model of experimental asthma to study the role of IL-12 during the development of bronchial inflammation. Administration of anti-IL-12p35 or anti-IL-12p40 mAb to previously OVA-sensitized BALB/c mice concomitantly with exposure to nebulized OVA, abolished both the development of bronchial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 50 publications
4
51
0
1
Order By: Relevance
“…In addition to the inhibition of OVA-induced pulmonary infiltration of eosinophils, lymphocytes and neutrophils, and increase in Th2 cytokine IL-4, IL-5 and IL-13 in the allergic airway (Ho et al 2012;Cheng et al 2011), artesunate was able to reduce the BALF level of a broad range of pro-inflammatory cytokines including IL-17, MCP-1, IL-12 p(40) and G-CSF. IL-12 p(40) has been linked to the full-blown asthma phenotype (Meyts et al 2006) and G-CSF is a major survival factor for neutrophils (Dai et al 2012). We have reported that BALF levels of sterols such as cholesterol, cholic acid and cortol declined in asthma model .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibition of OVA-induced pulmonary infiltration of eosinophils, lymphocytes and neutrophils, and increase in Th2 cytokine IL-4, IL-5 and IL-13 in the allergic airway (Ho et al 2012;Cheng et al 2011), artesunate was able to reduce the BALF level of a broad range of pro-inflammatory cytokines including IL-17, MCP-1, IL-12 p(40) and G-CSF. IL-12 p(40) has been linked to the full-blown asthma phenotype (Meyts et al 2006) and G-CSF is a major survival factor for neutrophils (Dai et al 2012). We have reported that BALF levels of sterols such as cholesterol, cholic acid and cortol declined in asthma model .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while some reports showed that administration of recombinant IL-12 ameliorates allergic airway inflammation (43), studies in IL-12-deficient mice showed that IL-12 deficiency does not alter the Th1/Th2 balance after secondary allergen exposure (44). Finally, a more recent report, in which neutralizing monoclonal antibodies against IL-12 were used, proposed an aggravating effect of IL-12 during allergen exposure (45). This shows how controversial the role of IL-12 remains and even suggests that inhibition of IL-12 production by lung DCs could be one of the mechanisms by which IMs prevent Th2 responses in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…This might also be relevant to asthma, for which a dual role for IL-12 was demonstrated in a murine model (37). It was shown that, despite the fact that IL-12 counteracts Th2 responses during allergen sensitization, it can enhance, on further allergen exposure, the recruitment of CD4 + T cells and granulocytes, as well as Th2 cytokines and chemokines; this unexpected proallergic role of IL-12 was not observed in IFN-g-deleted mice.…”
Section: Inhibition Of Stat1 Activation By Igamentioning
confidence: 99%